2016
DOI: 10.1007/s00345-016-1797-3
|View full text |Cite
|
Sign up to set email alerts
|

Medical students faced with related and unrelated living kidney donation: a stratified and multicentre study in Spain

Abstract: The attitude of medical students towards LKD is very favourable when it is the related kind of donation, and it is associated with factors of general knowledge about organ donation and transplantation and social interaction and religion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
2
2
0
1
Order By: Relevance
“…Probably, if the study is replicated, and we encourage researchers in the field of donation and transplantation to do so, in other countries and with lower donation rates, the results could be different (9-14). In Spain, as we had previously seen (15,16,17), the attitude toward organ donation among medical students is favorable and as we see in this study is very homogeneous throughout the Spanish territory. Our group (3) considers that the awareness of health professionals, both in training and active, is essential to maintain high donation rates, and the more quality data are, the better we can act in promotional campaigns and it will be able to go improving donation rates.…”
Section: Accepted Manuscriptsupporting
confidence: 77%
“…Probably, if the study is replicated, and we encourage researchers in the field of donation and transplantation to do so, in other countries and with lower donation rates, the results could be different (9-14). In Spain, as we had previously seen (15,16,17), the attitude toward organ donation among medical students is favorable and as we see in this study is very homogeneous throughout the Spanish territory. Our group (3) considers that the awareness of health professionals, both in training and active, is essential to maintain high donation rates, and the more quality data are, the better we can act in promotional campaigns and it will be able to go improving donation rates.…”
Section: Accepted Manuscriptsupporting
confidence: 77%
“…The results are similar with those performed in different populations of university students of health careers and countries previously and a majority position favorable to organ donation (2,3,7). Although, it is noteworthy, that the population under study is university medical students who in the future will exercise, if possible, a greater influence on decision making than other health professions analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…Authors: Ríos A [1][2][3][4] , López-Navas A 1,5 , Gutiérrez PR 6 , Gómez FJ 7 , Iriarte J 8 , Herruzo R 9 , Blanco G 10 , Llorca FJ 11 , Asunsolo A 12 , Sánchez P 13 , Fernández A 14 , de Jesús MT 15 , Martínez Alarcón L 1,3 , Lana A 16 , Fuentes L 17 , Hernández JR 18 , Virseda J 19 , Yelamos J 21 , Bondía JA 13 , Hernández AM 21 , Ayala MA 1,[22][23][24] , Flores-Medina J 5 , Carrillo J 1,2 , Sánchez Á 1 , Ramírez P [1][2][3][4] , Parrilla P [2][3] .…”
Section: Title Page: Do Religious Factors Influence the Attitude Towaunclassified
See 1 more Smart Citation
“…This finding is not unexpected as previous studies have reported the willingness of patients to accept a kidney from a donor especially from close relatives. 18,30,31 Participants who were unwilling gave reasons such as incompatibility of donated organ, uncertainties about their health status post-transplant, and uneasiness about the experience of kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%